2023
DOI: 10.3748/wjg.v29.i21.3362
|View full text |Cite
|
Sign up to set email alerts
|

Association of non-alcoholic fatty liver and metabolic-associated fatty liver with COVID-19 outcomes: A systematic review and meta-analysis

Abstract: BACKGROUND Non-alcoholic fatty liver disease (NAFLD) and metabolic-associated fatty liver disease (MAFLD) are on the rise like any other liver disease, and tend to affect 25% of the United States population. The impact of NAFLD and MAFLD on patients with coronavirus disease 2019 (COVID-19) remains unclear. AIM To identify the association of NAFLD and MAFLD with mortality, hospitalization, hospital length of stay, and supplemental oxygen utilization in COVID-19 patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…These results align with our previous study evaluating mortality in COVID-19 patients with pre-existing MAFLD. We found no significant difference in those with fatty liver disease than those without it, although MAFLD patients appear to have higher rates of hospital admissions and longer in-hospital stays compared to non-MAFLD patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results align with our previous study evaluating mortality in COVID-19 patients with pre-existing MAFLD. We found no significant difference in those with fatty liver disease than those without it, although MAFLD patients appear to have higher rates of hospital admissions and longer in-hospital stays compared to non-MAFLD patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, comorbidities such as obesity, diabetes, and fatty liver are associated with an elevated risk of developing severe COVID-19 [ 14 , 15 ]. Recent studies have demonstrated that individuals with MAFLD are at a four to six times higher risk of experiencing a worsening of their respiratory signs and symptoms compared to those who do not have fatty liver disease [ 15 ]. A study carried out in China discovered that severe COVID-19 was present in 70 out of 324 patients with fatty liver identified via abdominal computed tomography (CT) scans [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, comorbidities such as obesity, diabetes, and fatty liver are associated with an elevated risk of developing severe COVID-19 [14,15]. Recent studies have demonstrated that individuals with MAFLD are at a four to six times higher risk of experiencing a worsening of their respiratory signs and symptoms compared to those who do not have fatty liver disease [15].…”
Section: Introductionmentioning
confidence: 99%